De "salvajes" a heroicos: la construcción de la voz y la imagen del "indio Charrúa" desde 1830 a los inicios del siglo XX - Azpiroz, Andrés (2021)
The article analysis of the concept referring to the “indios charrúas” and the course it took progressively from the beginning of the Estado Oriental toward the 1st decades of the 20th century. From a conceptual history´s perspective, diverse meanings of the “charrúa”’s utterance were examined closely through written and iconographic sources. By reading the article, a very complex process is appreciated: how such a negative concept, associated to the word “savage” was transformed into a positive one, due to the integration of that group of “savages” to Uruguays national identity.